PENGARUH KESADARAN ANTI-FRAUD, KESESUAIAN KOMPENSASI, DAN MORALITAS INDIVIDU TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Setiana, Devira; Gunawan, Juniati (EBID: Ekonomi Bisnis Digital, 2023)
This research aims to test empirically the influence of anti-fraud awareness, the realization of peace, and individual morality on the tendency for accounting to occur in manufacturing companies operating in the automotive industry and rubber component production mining located in the Tangerang City area. The research method used is a quantitative method. The data used in this research is primary data. The data collection instrument used in this research was a questionnaire distributed to employees at one of the manufacturing industrial rubber part component companies in the Tangerang City area. This research is based on the Purposive Sampling method. The total research data obtained was 150 respondents. Hypothesis testing in this research uses multiple regression analysis techniques with a statistical approach operated through the SPSS Statistics version 25 program. The results showed that anti-fraud awareness, compliance compensation, and individual morality effect the tendency of accounting fraud.